Genome-wide identification and analysis of the HD-Zip transcription factor family in oats - Xu, Yiqun; Liu, Changlai (Frontiers in Molecular Biosciences, 2024)
IntroductionHD-Zip transcription factors are an important class of plant transcription factors involved in regulating plant growth and development as well as various stress responses. In order to explore the characteristics of oat HD-Zip transcription factors and their transcriptomic expression patterns under abiotic stress, this study identified members of the HD-Zip gene family in the oat genome through bioinformatics methods and analyzed their basic physicochemical properties, evolutionary relationships, conserved structural domains, gene duplication relationships, and expression profiles.Results74 HD-Zip gene sequences were identified in the oat genome, unevenly distributed in all chromosomes except the 4D chromosome. The 74 HD-Zip genes can be divided into four subfamilies (HD-Zip Ⅰ-Ⅳ), containing 30 (HD-Zip Ⅰ), 38 (HD-Zip Ⅱ), 4 (HD-Zip III), and 2 (HD-Zip IV) genes, respectively. The grouping of this study is completely consistent with the clustering results of family members in the oat HD-Zip gene phylogenetic tree, further supporting the reliability of the sequence grouping. In addition, there are significant differences in conserved motifs and gene lengths between subfamilies, but they are conserved within the same subfamily. Under drought and salt stress, the expression levels of a large number of oat HD-Zip genes were significantly induced or suppressed, indicating that these HD-Zip genes are likely to be involved in regulating the oat’s response to adversity.ConclusionsThe results of this study provide excellent candidate HD-Zip genes for the study of oat resistance, and provide a reference for oat gene improvement and genetic breeding.